EFFECT OF SOME ORGANIC NUTRIENTS AND NPK ON GROWTH PROPERTIES AND LEAVES CONTENTOF SOME NUTRIENTS OF GRAPE TRANSPLANTS CV. SUMMER ROYAL - & Hadi, Abdulraheem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was carried out in the nursery of the University of Baghdad- Al-Jadireya during the growing seasons of 2015 and 2016 t0 investigate the effects of two organic fertilizers; root stimulator(Essential plus 1-0-1) and Acadian extraction seaweed as well as NPK on the vegetative growth traits and some nutrient elements content in the leaves of grape transplants cv. Summer Royal. A factorial experiment was carried out according to the randomized complete block design(RCBD) with three replications. The experiment included 12 treatments, the first factor (organic nutrient) included adding the root stimulator to the soil at 4 ml.L-1 (A1), spraying the substance of the seaweed at 1 gm.L-1 (A2), and the interaction (A3), control (A0), and the second factor was spraying with mineral fertilizer TOTAL GRO (NPK) with three concentrations 0, 1.5, 3 g.L-1 marked as B0, B1, B2. The organic nutrient A3 significantly increased the leaf area chlorophyll, nitrogen phosphorus and potassium in the leaves as (32.76, 29.73%), (82.40,76.56%) (30.35, 23.59%), (56.17, 35.34%) and (26.73, 46.17%) for the two season respectily. B2 and B1 treatment were significantly influenced all the measured characteristics as compared to the control treatment, B2 treatment gave the maximum results in increasing the leaf area (48.75 ,50.91%)، leaves chlorophyll content (43.04 ,68.72%) nitrogen (17.22,11.48%)، phosphorus (26.7, 30.17%) and potassium (19.80 ,23.59%) for the two seasons,The maximum values were reached with significant changes in the all measured characteristics as compared to the control treatment at the interaction of the organic nutrient with the mineral fertilization especially A3B2 for the two seasons.We can conclude we can conclude that organic nutrition has positively affected the vegetative growth traits and leaves content of nutrients of Grape transplants cv. Summer Royal.